Pengaruh Media Film Animasi Terhadap Kemampuan Menyimak Pada Anak Usia 5-6 Tahun - Karina Salsabila Surya; Aini Loita; Gilar Gandana (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to determine the effect of animated film media on the listening skills of children aged 5-6 years. The study used an experimental method with a non-equivalent control group design involving 20 children from Pembina Kindergarten in Tasikmalaya City, divided into 10 children in the experimental group and 10 children in the control group. The experimental group was given treatment in the form of animated film presentations, while the control group used conventional learning media. Data were collected through observation sheets. The results showed a significant increase in the average score of the experimental group from 22.00 to 31.90. These findings indicate that animated film media can improve children's listening skills, because it combines visual and auditory stimuli that can facilitate understanding of information more effectively. The use of animated films also encourages children's active involvement in the learning process through clear narratives, characters close to their lives. This study recommends the use of animated film media as an alternative learning in early childhood education to develop children's listening skills optimally